Frequency Of Bacterial Co-Infections Isolated from Covid-19 Positive Patients From Tertiary Care Hospital Of Karachi - Khan, Fouzia Zeeshan; Fatima, Ambreen; Gohar, Hareem; Sajjad, Mehwish; Siddiqui, Mona; Naseem, Saima (Journal of Rawalpindi Medical College, 2023)
Objective: This study aims to determine the frequency of bacterial co-infections in COVID-19-positive patients. Methodology: A prospective cross-sectional study was conducted in the Department of Microbiology, Pakistan, from November 15, 2021, to April 15, 2022. Blood and respiratory tract samples were collected, including sputum, bronchial lavage, and tracheal aspirate. Clinical specimens were inoculated onto a Sheep blood agar plate, Chocolate agar plate (aerobic with 5% CO2), and MacConkey’s agar. Identification was followed by specific and standard microbiological protocols. COVID-19 was confirmed by qualitative PCR. Antimicrobial susceptibility testing was performed using the Kirby Bauer disc diffusion method. Results: A total of 202 clinical samples, including blood, sputum, tracheal aspirates, and bronchial lavage, were collected from COVID-19-positive patients. Male patients were more common in sputum and tracheal aspirates, while female patients were more common in blood cultures. The majority of patients were over 60 years of age. Acinetobacter baumannii was predominantly isolated from blood and tracheal aspirates, exhibiting multidrug resistance, but showing complete sensitivity towards Colistin. Klebsiella pneumonia exhibited high prevalence in sputum, with complete resistance observed in Cephalosporins and Co-trimoxazole. Conclusion: The study concludes a high frequency of superadded bacterial co-infections, caused most prominently by Acinetobacter baumannii, Klebsiella pneumonia, and Pseudomonas aeruginosa. The majority of these are multidrug-resistant pathogens, therefore, urgent action is required to control the spread of nosocomial infections by resistant strains, which are responsible for the high mortality rate among COVID-19 critical patients.